DESIGN FABRICATION AND EVALUATION OF MICROBEADS FOR CONTROLLED RELEASE USING NATURAL POLYMERS - JAMDADE S. M; KASLIWAL R. H. (International Journal of Pharma and Bio Sciences, 2013)
Diclofenac sodium is an Non-steroidal anti-inflammatory drugs, having an elimination half-life of 1-2 hrs. The objective of the study is to prepare Diclofenac sodium Microbeaads using Natural Polymers in different concentrations. For this purpose calcium ions were used as cross linking agents in formulation of alginate-guar gum-pectin, alginate-guar gum-lecithin and alginate-pectin-lecithin Microbeads by ionotropic gelation method. The Microbeads were investigated for swelling index, dynamic water uptake, entrapment efficiency, particle size, SEM and in-vitro release studies. The Microbeads formulations showed acceptable properties and complied with in-house specifications for tested parameters. The results of in-vitro dissolution studies indicated that formulation DF4, DF6 and DF7 could extend the drug release up to 12 hours. While an increase in the concentration of sodium alginate and other polymer dispersions increased sphericity, size distribution, mean particle size. The successful formulation of the study, exhibited satisfactory drug release (DF4, DF6 and DF7) which suggests sustained/controlled release profile.